Exploring the Role of Social Support between Discharge Teaching and Readiness for Discharge in Ocular Fundus Disease Patients: A Cross-Sectional Study - Jie Zhang; Shuyu Yao; Feifei Huang; Yan Zhang; Nanqi Huang; Huiming Xiao; Jingping Zhang; Yu Lian (Journal of Ophthalmology)
Background. This study aims to evaluate the quality of discharge teaching and readiness for discharge of fundus disease patients treated with day surgery and understand the role of social support between them. Methods. This was a cross-sectional descriptive correlational survey. Through convenient sampling, fundus disease patients treated with day surgery from Zhongshan Ophthalmic Center, China, were recruited. Data were collected using demographic and disease-related information, quality of discharge teaching scale, readiness for hospital discharge scale, and social support scale. Results. 255 fundus disease patients treated with day surgery were recruited at last. The mean total score of readiness for discharge, quality of discharge teaching, and social support in patients with fundus disease were 157.91 (SD = 26.68), 122.97 (SD = 21.55), and 36.32 (SD = 7.60), respectively. Participants with stronger social support had better discharge teaching and then had higher readiness for discharge. Social support played a partial mediator role in the relationship between discharge teaching and readiness for discharge. The mediation effect ratio was 5.5%. Conclusions. The quality of discharge teaching and social support among fundus disease patients who underwent day surgery was relatively high, and readiness for discharge was good. Social support is essential for the quality of discharge teaching and the improvement of discharge readiness. Clinical nurses need to provide appropriate guidelines to help patients seek effective support and improve quality of discharge teaching to enhance the readiness for discharge of fundus disease patients treated with day surgery.